Flurnamen und Konsorten : Kleine onomastische Schriften - Scheuermann, Ulrich (2023)
Linguists interested in the history of languages as well as historians focussing on regional studies favorably resort to onomatology in order to prove the evidence or insights of their own research. Onomastics, in itself an interesting subject, can provide relevant data regarding questions of identity of both individuals and social groups, such as village communities, for example. The volume on hand covers several decades of texts by Ulrich Scheuermann presenting his onomastical research on fieldnames predominantly from Lower Saxony. Not only is this collection of essays a knowledgeable introduction into practical onomastical methods which require critical assessment of sources, detailed etymological and grammatical analysis as well as solid local knowledge. With their variety of findings the essays also illustrate the close connections between field and place names and names of deserted settlements or villages.